Corporeality and Askesis: Ethics and Bodily Practice in Gregory of Nyssa’s Theological Anthropology - Cadenhead, Raphael (Studies in Christian ethics, 2013)
This article seeks to extend and refine Alastair MacIntyre’s moral theory of virtue ethics, by probing behind the Benedictine Rule—so fulsomely invoked at the end of After Virtue—to the ascetical theology of the noted, Eastern, ‘Cappadocian’ theologian of the fourth century: Gregory of Nyssa. I shall argue that Gregory’s vision of ascetical bodily practice complicates MacIntyre’s contemporary appropriation of virtue ethics. It does so by underscoring the diachronic, developmental character of personal ethical maturation—a theme which finds no expression in MacIntyre’s otherwise sophisticated account of ‘narrative’.